ON PROVIDING THE VOLUNTEER ASSISTANCE TO THE VULNERABLE GROUPS OF POPULATION IN THE SOCIAL SUPPORT SYSTEM - Kashytskyi, Andriy (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to determine a place of the volunteer assistance to the vulnerable groups of population in the social support system. Research methods: formal and logical, dogmatic, comparative, systemic and structural methods were used. Results: it was concluded that volunteering plays an important role in the social support system, that consists in voluntarily assuming the obligations of the social service provider to persons/families who exist in difficult life circumstances. Discussion: the tense socio-economic situation, deterioration of the quality of life of the population, emergence of new risk groups in the context of war leads to the expansion of social support for the population, including through the strengthening of volunteer activities designed to complement the services provided by the state.